2014
DOI: 10.1111/1754-9485.12242
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated radiation treatment following mastectomy in early breast cancer: The Christchurch experience

Abstract: The high local control rate with HFRT, combined with acceptable toxicity and the practical benefits of a shorter treatment time, supports its ongoing use in the eligible patient group. A randomised controlled trial would be necessary to more completely assess the acute and long-term toxicity of HFRT compared with standard fractionation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 9 publications
3
12
0
Order By: Relevance
“…One series reports a 5-year local recurrence-free survival of 97.6%, 5-year overall survival of 74.7% and 5-year breast cancer survival of 77.7%. 8 This compares favourably with figures for CFRT after a mastectomy. Late toxicity and especially cardiac toxicity for HFRT following a mastectomy, however, is not well documented.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…One series reports a 5-year local recurrence-free survival of 97.6%, 5-year overall survival of 74.7% and 5-year breast cancer survival of 77.7%. 8 This compares favourably with figures for CFRT after a mastectomy. Late toxicity and especially cardiac toxicity for HFRT following a mastectomy, however, is not well documented.…”
Section: Introductionsupporting
confidence: 52%
“…Although randomised evidence comparing HFRT versus CFRT following mastectomy is lacking, long term outcome data from HFRT series indicate good breast cancer outcomes. One series reports a 5‐year local recurrence‐free survival of 97.6%, 5‐year overall survival of 74.7% and 5‐year breast cancer survival of 77.7% . This compares favourably with figures for CFRT after a mastectomy.…”
Section: Introductionmentioning
confidence: 96%
“…This meta-analysis indicated that HFRT and CFRT were equally effective with respect to overall survival (OS), disease-free survival (DFS), locoregional recurrence (LRR), and distant metastasis (DM) after breast mastectomy. In recent small retrospective cohort studies, HF PMRT was shown to be effective with acceptable toxicity [38][39][40][41]. In a recent phase 2 trial [42], 67 women with clinical stage II to IIIa breast cancer who received a HF PMRT regimen of 36.6 Gy over 11 fractions to the chest wall and the draining regional lymph nodes with a scar boost of 4 fractions of 3.33 Gy revealed that after a median follow-up of 32 months, patients with isolated ipsilateral chest wall tumor recurrences were 3.0%, the 3-year estimated overall survival was 92.0% (95% CI, 78.9~97.1), the 3year estimated local recurrence-free survival was 89.2% (95% CI, 74.8~95.6), the 3-year estimated distant recurrence-free survival was 90.3% (95% CI, 79.7~95.6), and low toxicity was reported.…”
Section: Discussionmentioning
confidence: 99%
“…15 Ko et al, analyzed retrospective data of 133 PMRT patients in Christchurch Hospital, New Zealand and reported high local control rate (97.6%) and less toxicities with HFRT (40 Gy/16 fractions). 16 Elsayed et al, published another prospective trial of 47 patients receiving PMRT with conventional versus hypofractionation (42.72 Gy/16F). 17 The results were equivalent in terms of OS, DFS and adverse effects and observed HFRT to be advantageous in terms of reduced workload and cost of treatment.…”
Section: Discussionmentioning
confidence: 99%